The prediction algorithm of the technical state of an object by means of fuzzy logic inference models - Kuvayskova, Yu. E. (Procedia engineering, 2017)
The prediction algorithm of the technical state of an object was elaborated to predict emergencies at object functioning and to provide urgent steps required to control the object. The technical state is described by a set of indices represented by a system of time series. The adequate mathematical model is built by means of an adaptive regression modeling for the system of time series. The model is used to predict the object indices. The predicted values of indices are analyzed by means of fuzzy logic and predicted state of an object is deduced as a fuzzy term.